2015
DOI: 10.1177/0963662515597195
|View full text |Cite
|
Sign up to set email alerts
|

Defining criteria for good environmental journalism and testing their applicability: An environmental news review as a first step to more evidence based environmental science reporting

Abstract: While the quality of environmental science journalism has been the subject of much debate, a widely accepted benchmark to assess the quality of coverage of environmental topics is missing so far. Therefore, we have developed a set of defined criteria of environmental reporting. This instrument and its applicability are tested in a newly established monitoring project for the assessment of pieces on environmental issues, which refer to scientific sources and therefore can be regarded as a special field of scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 49 publications
3
18
0
3
Order By: Relevance
“…This system is characterized by a strong degree of professionalization, a rather competitive and shrinking newspaper market, a diverse ensemble of newspapers reflecting all major political positions and a rather low affiliation of the newspaper market to the political system. Our finding of an increasing and increasingly sophisticated use of sustainability terminology reflects different small‐scale, but intensive efforts in the German media system that seek to promote qualification, education and quality development among environmental and sustainability journalists (Braun et al , ; Rögener and Wormer, ). These initiatives, however, are ambiguous in the sense that a minority of professionalized and dedicated sustainability journalists is facing a vast majority of journalists and media companies that struggle with precarious structures of a shrinking mass media market (Dernbach, ): a development that is widely considered as a serious impediment for a sophisticated journalistic engagement with complex issues such as sustainability or sustainable development (Humburg et al , ).…”
Section: Discussionmentioning
confidence: 87%
“…This system is characterized by a strong degree of professionalization, a rather competitive and shrinking newspaper market, a diverse ensemble of newspapers reflecting all major political positions and a rather low affiliation of the newspaper market to the political system. Our finding of an increasing and increasingly sophisticated use of sustainability terminology reflects different small‐scale, but intensive efforts in the German media system that seek to promote qualification, education and quality development among environmental and sustainability journalists (Braun et al , ; Rögener and Wormer, ). These initiatives, however, are ambiguous in the sense that a minority of professionalized and dedicated sustainability journalists is facing a vast majority of journalists and media companies that struggle with precarious structures of a shrinking mass media market (Dernbach, ): a development that is widely considered as a serious impediment for a sophisticated journalistic engagement with complex issues such as sustainability or sustainable development (Humburg et al , ).…”
Section: Discussionmentioning
confidence: 87%
“…Over the last decade science journalism has undergone fundamental changes due to budget and personnel cuts that have led to the closure of many science sections at newspapers (Brumfiel, 2009;Rögener and Wormer, 2017). Particularly here, it can be observed that effective -and, despite all the doubts expressed, sometimes qualitatively valuablepublic relations carried out by universities and research institutions has spearheaded the media coverage of certain areas of science (Rögener and Wormer, 2017;Berg, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…Following the observations made by Berinsky and Kinder (2006) that storytelling can guide the audience's own reflections on and interpretations of an issue, modern PR and marketing have highly effectively used storytelling for image building and to increase acceptance of certain issues and products (Sammer, 2014). The PR and marketing work carried out by companies and NGOs is able to promote individual messages by using complex communication models based on storytelling as well as issue management and agenda-building techniques.…”
Section: The Role Of Science Pr and Other Actors In Ccs-related Commumentioning
confidence: 99%
See 1 more Smart Citation
“…Rückmeldungen aus den Begutachtungsprozessen wurden in mehreren Konsensfindungsrunden der Redaktionsleitungen für die 3 Teilprojekte "Medien-Doktor Umwelt" (mit eigenem Kriterienkatalog), "Medien-Doktor Ernährung" und "Medien-Doktor Medizin/Gesundheit" diskutiert sowie retrospektiv mit Rückmeldungen aus der Bewertung der vorangegangenen n = 310 Gutachten (Zeitraum Nov. 2010 [37]. Quelle: eigene, angepasste Darstellung aus [16] Entwicklung von Kriterien zur Bewertung ernährungsjournalistischer Beiträge mit Gesundheitsbezug Die Entwicklung und Erprobung von Qualitätskriterien für den Ernährungsjournalismus orientiert sich am Entstehungsprozess eines Katalogs für die Umweltberichterstattung [19]. In einem ersten Schritt wurde dafür in einem Set von Ernährungs-, Kommunikationsund sozialwissenschaftlichen Fachzeitschriften sowie Webseiten fachjournalistischer Verbände nach Kriterien oder Empfehlungen für den Ernährungsjournalismus gesucht (Liste kann angefordert werden).…”
Section: Quality Research In Journalism • Medical Journalism • Nutritunclassified